2011
DOI: 10.1136/aim.2010.003475
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Reporting on Randomised Controlled Trials of Auriculotherapy for Pain

Abstract: Objective The authors investigated the quality of reporting for randomised controlled trials of auriculotherapy for pain before and after the implementation of the Consolidated Standards of Reporting Trials (CONSORT) and Standards for Reporting Interventions in Controlled Trials of Acupuncture (STRICTA) guidelines. Methods The authors identifi ed randomised controlled trials of auriculotherapy that measured pain or pain medication use as a primary outcome and were published in English in peer-reviewed journals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(17 reference statements)
2
3
0
Order By: Relevance
“…In the evaluation of acupuncture trials performed by Prady et al [27], the authors concluded that reporting of CONSORT items had improved after the introduction of CONSORT but that the introduction of STRICTA did not improve the reporting of STRICTA items. However, another evaluation of auriculotherapy trials [23] came to similar conclusions with ours. Maybe the introduction of STRICTA and CONSORT statement improved the overall quality of reporting in our research.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the evaluation of acupuncture trials performed by Prady et al [27], the authors concluded that reporting of CONSORT items had improved after the introduction of CONSORT but that the introduction of STRICTA did not improve the reporting of STRICTA items. However, another evaluation of auriculotherapy trials [23] came to similar conclusions with ours. Maybe the introduction of STRICTA and CONSORT statement improved the overall quality of reporting in our research.…”
Section: Discussionsupporting
confidence: 88%
“…We found evidence that quality of reporting of the overall CONSORT items was general with median OQS 8 which was more than half of its total score 15; quality of reporting of the STRICTA items was good with median OQS 12 which was more than 70% of its total score 17; however, it is poor quality for the reporting of key methodological items with median MIS 1 which was 33% of its total score. Similar results were reported in some published studies [23,24]. Some studies found that the quality of reporting in RCTs on Chinese medicine remained poor (mainly in key methodological items), but had improved over time [25,26].…”
Section: Discussionsupporting
confidence: 84%
“…An inappropriate study design could lead to exaggeration of the clinical outcome [23, 24, 43, 44], which has been reported in a few other quality assessment studies [45, 46]. In reports of RCTs of Chinese medicine, the quality of the reporting of the methodology is poor, warranting the use of CONSORT guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown no cost savings in back care services after 1 year among groups receiving acupuncture compared with patients who received massage or self-care [43] or have shown a modest increase in overall treatment costs [44, 45] when in adjunct to usual care. Although auricular acupuncture, which can leave the needle in situ for up to 1 month, may solve the problems of frequent therapist office visits [18, 46], it must be administered by a licensed therapist. If APA can achieve treatment effects comparable to acupuncture, the use of APA will receive far more application in clinical settings.…”
Section: Discussionmentioning
confidence: 99%